2015
DOI: 10.1002/asna.201412162
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field measurements of ϵ Eridani from Zeeman broadening

Abstract: We present new magnetic field measurements of the K2 main-sequence star Eri based on principal components analysis (PCA) line-profile reconstructions. The aim of this paper is to quantify the surface-averaged magnetic field and search for possible variations. A total of 338 opticaléchelle spectra from our robotic telescope facility STELLA with a spectral resolution of 55 000 were available for analysis. This time-series was used to search for the small line-profile variations due to a surface magnetic field wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…This quantity is consistent with our B f , as well as Valenti et al (1995) and Rueedi et al (1997), but is much smaller than our B f and that of Valenti et al (1995). While some discrepancies between studies are likely due to systematic errors or underestimated uncertainties, the results of Lehmann et al (2015) suggest that there is also important temporal variability to the Zeeman broadening of Eridani.…”
Section: Zeeman Broadeningsupporting
confidence: 93%
See 1 more Smart Citation
“…This quantity is consistent with our B f , as well as Valenti et al (1995) and Rueedi et al (1997), but is much smaller than our B f and that of Valenti et al (1995). While some discrepancies between studies are likely due to systematic errors or underestimated uncertainties, the results of Lehmann et al (2015) suggest that there is also important temporal variability to the Zeeman broadening of Eridani.…”
Section: Zeeman Broadeningsupporting
confidence: 93%
“…From our multi-component model we calculate i B i f i = 542 ± 219, although this quantity is dominated by the larger field bins with small, uncertain filling factors, thus we consider it effectively an upper limit. More recently, Lehmann et al (2015) investigated Zeeman broadening in Eridani spectra spanning 5 yr, using an approach based on principal component analysis. These authors report B f values varying between 124 ± 25 and 230 ± 21 G, possibly varying with a 3-yr cycle (e.g.…”
Section: Zeeman Broadeningmentioning
confidence: 99%
“…We separated the short-time variation of the effective magnetic field, due to stellar rotation, from the long-term variation through the coefficient A 0 (defined in Eq. 12); we used a Fourier transform to discover that the best-fit period of the variation of A 0 (P 1 = 1099 ± 71 d) is close to the short cycle period in the S-index found by Metcalfe et al (2013) and to the period of the magnetic field found by the analysis of the Zeeman broadening (Lehmann et al 2015). Direct measurements of the effective magnetic field thus open up the possibility to determine the periods of the cycles of active cool stars.…”
Section: Resultsmentioning
confidence: 68%
“…It is instructive to compare the results of the spectropolarimetric modeling with the measurements of total magnetic flux from Stokes I . Such measurements, based on principal component analysis of high and low Landé‐factor Stokes I line profiles, were presented for ϵ Eridani by Lehmann et al (). Clear short‐term variations of the surface‐averaged magnetic field of up to few tens of Gauss were detected together with evidence for a 3‐year cycle (see Figure ).…”
Section: Magnetic Cycles Of Solar‐type Starsmentioning
confidence: 99%